Transferring skills in quality collaboratives focused on improving patient logistics - Anne Marie Weggelaar-Jansen; Jeroen van Wijngaarden (BMC, 2018)
Abstract Background A quality improvement collaborative, often used by the Institute for Healthcare Improvement, is used to educate healthcare professionals and improve healthcare at the same time. However, no prior research has been done on the knowledge and skills healthcare professionals need to achieve improvements or the extent to which quality improvement collaboratives help enhance both knowledge and skills. Our research focused on quality improvement collaboratives aiming to improve patient logistics and tried to identify which knowledge and skills are required and to what extent these were enhanced during the QIC. Methods We defined skills important for logistic improvements in a three-phase Delphi study. Based on the Delphi results we made a questionnaire. We surveyed participants in a national quality improvement collaborative to assess the skills rated as 1) important, 2) available and 3) improved during the collaborative. At two sense-making meetings, experts reflected on our findings and hypothesized on how to improve (logistics) collaboratives. Results The Delphi study found 18 skills relevant for reducing patient access time and 21 for reducing throughput time. All skills retrieved from the Delphi study were scored as 'important' in the survey. Teams especially lacked soft skills connected to project and change management. Analytical skills increased the most, while more reflexive skills needed for the primary goal of the collaborative (reduce access and throughput times) increased modestly. At two sense-making meetings, attendees suggested four improvements for a quality improvement collaborative: 1) shift the focus to project- and change management skills; 2) focus more on knowledge transfer to colleagues; 3) teach participants to adapt the taught principles to their own situations; and 4) foster intra-project reflexive learning to translate gained insights to other projects (inter-project learning). Conclusions Our findings seem to suggest that Quality collaboratives could benefit if more attention is paid to the transfer of 'soft skills' (e.g. change, project management and communication skills) and reflexive skills (e.g. adjusting logistics principles to specific situations and inter-project translation of experiences).